Dating the onset of motion on the Sagaing fault: Evidence from detrital zircon and titanite U-Pb geochronology from the North Minwun Basin, Myanmar - C. K. Morley (2019)
© 2019 Geological Society of America. The onset of dextral motion along SE Asia's largest active strike-slip fault, the Sagaing fault in Myanmar, has been the subject of considerable controversy, with estimates ranging from the Miocene-Pliocene boundary to possibly the late Eocene, along with displacement magnitude estimates ranging between 100 km and 400+ km. A recently identified synkinematic basin formed at a releasing bend in one of the fault strands in northern Myanmar was dated in this study using the maximum depositional ages from detrital zircons and titanites, giving an Oligocene age (28-27 Ma). This dates the onset of motion on the fault zone and favors the high-displacement models (>400 km). The higher displacement and older history of the Sagaing fault impact how the western Burma terrane interacted with the basins in the eastern Andaman Sea and indicate that high strike-slip displacements and shortening occurred during the late-stage development of the Indo-Burma Ranges.